Competency-based pharmacy education: Implementations of performance assessment - Ozhan, Gul; Akalin, Emine; Yildizli, Hulya; Sirin, Ozlem Kurt; Tuncay, Huseyin Onur; Eter, Ozge Soylu; Cevher, Erdal (Istanbul Univ, Fac Pharmacy, 2025)
Background and Aims:Determining the knowledge and competencies of professionals trained in higher education is crucial for ensuring standardisation and guaranteeing and sustaining quality. The Turkish Council of Higher Education has defined national professional qualifications in the field of pharmacy. Faculties providing pharmacy education are also required to plan and conduct their programmes according to these defined competency outcomes. Methods:This studywill provide examples of assessment practices in the competency-based education (CBE) model adopted atthe Istanbul University Faculty of Pharmacy within the framework of these obligations. Results: The fact that this competency performance assessment system is the first application in Turkey to evaluate the cognitive, affective, and psychomotor behaviours of students studying pharmacy is significant in terms of being a guide and example for national and international pharmacy education. CBE practices, which provide important perspectives in training qualified pharmacists suitable for the needs of both today and the future, also highlightthe importance and quality of field and faculty cooperation. The study also offers recommendations to programme developers and implementers. Conclusion: Considering the difficulties experienced in making fundamental changes in curricula, it is evident that the main requirement is to bring faculty, instructor, student, and external stakeholder collaborations to the table with transparent, measurable, and evaluable criteria in the implementation of such competency-based programmes. Highlighting these dynamics in the programmes to be developed is importantforthe healthy implementation ofthe programme.
Keywords: Competency Based Education (CBE); Competency Based Pharmacy Education (CBPE); Case Based Learning (CBL); Assessment Practises